PERAN SERTA ORGANISASI PEMBERDAYAAN KESEJAHTERAAN KELUARGA (PKK) DALAM UPAYA PENCEGAHAN DAN PENANGANAN DINI KORBAN KEKERASAN - Anak Agung Istri Ari Atu Dewi; Anak Agung Ketut Sukranatha; I Gusti Ayu Putri Kartika; Gusti Ayu Kade Komalasari (Jurnal Aktual Justice, 2019)
The specific purpose and target of this research is to determine the role of family welfare empowerment organizations (PKK) in the prevention and early handling of women and children victims of violence. The reason for researching this topic is the increase in the number of victims of violence against women and children every year. Based on data from the Ministry of Women's Empowerment and Child Protection, it is shown that since 2012 it has increased from 18,718 to 54,041 cases in June 2017 and until February 2018 it has shown 374 cases of violence against women and children. In this case, the Government is responsible for providing optimal services needed by victims, both medical, psychological, and legal assistance in an effort to recover their condition. The government in providing services to victims should cooperate and partner with the community, especially in the prevention and early handling of victims of violence. Prevention and early handling of victims of violence at the village level can empower family welfare empowerment organizations (PKK) which are government partners that are considered effective in the prevention and early handling of women and children victims of violence in their areas. Based on these reasons, it is necessary to study in depth the role of the PKK organization in preventing and early handling of women and children victims of violence. To achieve specific goals and targets in this study, the research method used is a normative research method with a statue approach and a conceptual approach.The results of the study provide an overview 1) there is a clear regulation in the laws and regulations related to the participation of the PKK in preventing and early handling of victims of violence, what needs to be further regulated is regulation in the form of Village Regulations and customary law (awig-awig) related to the participation of PKK and indigenous women in the prevention and early handling of victims of violence. 2) the procedures for preventing and early handling of victims of violence need to be stated in the operational standards in the village and the traditional village paparem.